Facile high-yield synthesis and purification of lysine-modified graphene oxide for enhanced drinking water purification. Issue 70 (12th August 2022) - Mantovani, Sebastiano; Khaliha, Sara; Marforio, Tainah Dorina; Kovtun, Alessandro; Favaretto, Laura; Tunioli, Francesca; Bianchi, Antonio; Petrone, Gaetana; Liscio, Andrea; Palermo, Vincenzo; Calvaresi, Matteo; Navacchia, Maria Luisa; et al.
Abstract : Lysine-modified graphene oxide is synthesized and exploited as an adsorbent of emerging contaminants in drinking water. Abstract : Lysine–covalently modified graphene oxide (GO-Lys) was prepared by an innovative procedure. Lysine brushes promote enhanced adsorption of bisphenol A, benzophenone-4 and carbamazepine contaminants from tap water, with a removal capacity beyond the state of the art.